The ‘extended’ Atkinson family and changes in the expenditure distribution. Spain 1973/74-2003 - Goerlich-Gisbert, Francisco J.; de la Vega, Casilda Lasso; Urrutia, Ana Marta (Journal of Income Distribution®, 2009)
This paper emphasizes the properties of a family of inequality measureswhich extends the Atkinson indices and is axiomatically characterizedby a multiplicative decomposition property where the withingroupcomponent is a generalized weighted mean with weights summingexactly to 1. This family contains canonical forms of all aggregativeinequality measures, each bounded above by 1, has a usefuland intuitive geometric interpretation and provides an alternative dominancecriterion for ordering distributions in terms of inequality.Taking the Spanish Household Budget Surveys (HBS) for 1973/74,1980/81, and 1990/91 and the more recent Continuous HBS for 2003,we show the advantages and possibilities of this extended family inregard to completing and detailing information in studies of inequalityfocussing on the tails of the distribution and on the changes in the distributionwhen the population is partitioned into population subgroups.